Childhood death rates declined in Sweden from 2000 to 2014 but deaths from external causes were not always investigated. (6th April 2018) - Otterman, Gabriel; Lahne, Klara; Arkema, Elizabeth V.; Lucas, Steven; Janson, Staffan; Hellström‐Westas, Lena
Abstract: Aim: Countries that conduct systematic child death reviews report a high proportion of modifiable characteristics among deaths from external causes, and this study examined the trends in Sweden. Methods: We analysed individual‐level data on external, ill‐defined and unknown causes from the Swedish cause of death register from 2000 to 2014, and mortality rates were estimated for children under the age of one and for those aged 1–14 and 15–17 years. Results: Child deaths from all causes were 7914, and 2006 (25%) were from external, ill‐defined and unknown causes: 610 (30%) were infants, 692 (34%) were 1–14 and 704 (35%) were 15–17. The annual average was 134 cases (range 99–156) during the study period. Mortality rates from external, ill‐defined and unknown causes in children under 18 fell 19%, from 7.4 to 6.0 per 100 000 population. A sizeable number of infant deaths (8.0%) were registered without a death certificate during the study period, but these counts were lower in children aged 1–14 (1.3%) and 15–17 (0.9%). Conclusion: Childhood deaths showed a sustained decline from 2000 to 2014 in Sweden and a quarter were from external, ill‐defined or unknown causes. Systematic, interagency death reviews could yield information that could prevent future deaths. Abstract :